Let's Measure the Liver Better: A Pilot Study Assessing Inter-Rater Reliability When Measuring the Liver Volume Using Sonography. (May 2022) - Hellmann, Rivka; Struk, Iryna; Haddash, Dalal; Jalloh, Fatmata; Pan, Emily
Objective: When measuring the liver sonographically, liver volume measurement (LVM) is not routinely performed, though considered the gold standard on CT. The objective of this study is to encourage the sonography community to obtain an LVM instead of a single linear measurement on ultrasound, so as not to subject patients to the potentially harmful radiation exposure of a CT scan when assessing liver size. This study compared the consistency and accuracy between expert and novice sonographers in obtaining an LVM on sonography. Materials and Methods: Both groups obtained linear and LVM on 30 participants and calculated LVM using the formula Liver Volume (cc) = 343.71 + (0.84 × ABC). Results: Both groups took longer to obtain LVM than linear, P < .0001. Novices and experts obtained an LVM in a similar amount of time. More consistency was observed among experts when scanning participants in the lower BMI ranges. Novice sonographers' LVMs were consistent with experts' only in the lowest BMI range of this study. Conclusion: Groups acquired LVM in similar amounts of time, showing LVM is easy to teach and learn, and has good inter-rater reliability. Difference for both groups to obtain LVM over linear was only 38 seconds. Consequently, it is prudent to incorporate LVM into abdominal ultrasound protocols.